European consumers' readiness to adopt insects as food. A review. (August 2019) - Mancini, Simone; Moruzzo, Roberta; Riccioli, Francesco; Paci, Gisella
Abstract: Edible insects seem one of the more probable responses to the increased quantity of food proteins needed in future prospective related to the increase of human population, mainly in developing countries. Introduction of entomophagy in developed countries, especially in Europe and North America, could help this trend and drive the world food economy to reach that goal. Few articles were published on acceptability of edible insect in European countries, with a large variability of methodologies used. Furthermore, both structure and unstructured (or semi-structured) techniques were analysed and compared. Through this review article, we analysed the different methodologies conducted on European consumers and categorised the studies in relation to the type of analysis chosen, data collection and results obtained. Limitation of the research studies and future recommendations were explored leading to better investigate consumers' acceptance. Graphical abstract: Unlabelled Image Highlights: We reviewed research articles on edible insects in the context of European consumers. We focused on forty-one articles without restriction of year of publication. We categorised researches' methodologies and gathered data into clusters. We reviewed both structured and unstructured techniques. We summarized the results of the research studies.